Kriteria Iktikad Baik pada Klausul Disclaimer dalam Kontrak Elektronik - Kinan Kalam Khalifa (Faculty of Law Hang Tuah University, 2024)
Electronic contracts are one form of development in the use of contracts. Electronic contracts are commonly used by society in buying and selling activities through electronic systems. Buying and selling through electronic systems is considered to have many advantages, namely increasing their income, market share and profits. However, behind these advantages, there is still a problem, namely the inclusion of a disclaimer clause by the seller in the electronic sale and purchase contract that is not in good faith. This results in losses for consumers because of the difficulty of filing a claim to ask for accountability to the seller. This study uses literature research related to the rules, legislation, and the data collected is analyzed descriptively. The existence of a disclaimer clause must be followed in good faith in accordance with Article 18 paragraph (1) of Law no. 8 of 1999 concerning Consumer Protection or Consumer Protection Law (CPL) regarding the limitation of the disclaimer clause. The use of the disclaimer clause by sellers who do not have good intentions must be held accountable by providing compensation to the injured party (vide Article 19 paragraph (1) CPL).